(untitled) (The Research of Medical Science Review, 2025)
Non‐muscle invasive bladder cancer (NMIBC) represents about 75% of these cases (Bladder cancer is one of the most prevalent malignancies worldwide) [1]. NMIBC is both diagnostic and therapeutic through transurethral resection of bladder tumor (TURBT); however, there are complications of TURBT such as bleeding and bladder perforation (BP) [2, 3]. Because the depth of resection is an important determinant of immediate and long-term complications, the need to intraoperatively assess the integrity of the bladder wall is critical. This is a prospective clinical study to evaluate the intraoperative depth of bladder perforation using the Endoscopic Perforation Depth Scale (EPDS) in patients who undergo TURBT, while the contributing clinical factors (patient demographics, tumor characteristics, and comorbidities) were correlated with the risk and severity of BP. After institutional review board and CPSP approval, a total of 190 patients (30–75 years) were enrolled. WHO criteria was used to calculate sample size based on previously reported deep grade 0 of 58.9% [4]. Prospectively collected, intraoperative grading was performed by the senior surgeon supervising the resident. SPSS (v24) was used for statistical analysis. The study also shows that standardized BP assessment on the EPDS can indicate subtle variations in perforation depth and may act as a quality indicator for TURBT. Our results find that EPDS grade is a function of several clinical factors (size of tumor is the most important) and surgeon experience. This study emphasizes well-accepted intraoperative grading methods so that management of patients as well as the allocation of resources and the clinical outcome could be improved. [5–7].